2008
DOI: 10.1103/physrevb.78.214504
|View full text |Cite
|
Sign up to set email alerts
|

Surface superconductivity, positive field cooled magnetization, and peak-effect phenomenon observed in a spherical single crystal of niobium

Abstract: We report the observation of surface superconductivity as well as positive field cooled magnetization, along with peak-effect phenomenon in ac and dc magnetization measurements in a high-purity spherical single crystal of niobium. We study how the surface superconductivity and the positive field cooled magnetization evolve over the field ͑H͒ and the temperature ͑T͒ phase space. We suggest that the observed evolution in the strength of the positive field cooled magnetization signal may be understood on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…However, a conspicuous change in temperature dependence of χ can be noted to happen near T * VL . Such a change is often ascribed 10 to the crossover between the shielding response in the bulk to the shielding response from the surface superconductivity. In the present case, where we witness the PMFC signal above 8 K in dc magnetization data, it can be noted that M/ H is negative (cf.…”
Section: E Ac Susceptibility Measurements In Ca 3 Rh 4 Sn 13mentioning
confidence: 99%
See 4 more Smart Citations
“…However, a conspicuous change in temperature dependence of χ can be noted to happen near T * VL . Such a change is often ascribed 10 to the crossover between the shielding response in the bulk to the shielding response from the surface superconductivity. In the present case, where we witness the PMFC signal above 8 K in dc magnetization data, it can be noted that M/ H is negative (cf.…”
Section: E Ac Susceptibility Measurements In Ca 3 Rh 4 Sn 13mentioning
confidence: 99%
“…Invoking the possible special d-wave symmetry of the superconducting order parameter in HTSC materials, different models, such as the presence of an odd number of π junctions in a loop leading to spontaneous circulating currents producing a positive magnetization signal, the presence of Josephson junctions (π or 0), spontaneous supercurrents due to vortex fluctuations or an orbital glass, 5,6 were proposed to explain the PME. However, the subsequent observation of positive magnetization even in conventional s-wave superconductors, such as moderately pinned Nb discs, 7,8 nanostructured Al discs, 9 and a weakly pinned spherical single crystal 10 of Nb, has indicated that the origin of positive magnetization on field cooling in these materials is perhaps related to flux trapping [11][12][13][14] and its possible subsequent compression. 11,13,14 Magnetic flux can get trapped in the bulk of a superconductor below T c , as the preferential flux expulsion from the superconducting boundaries can lead to a flux-free region near the sample edges, which would grow as the sample is further cooled.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations